2015
DOI: 10.1097/ajp.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

A Case-controlled Investigation of Pain Experience and Sensory Function in Neuronal Ceroid Lipofuscinosis

Abstract: Objectives This case-control study explored pain experience and expression among individuals with Neuronal Ceroid Lipofuscinosis (NCL) through parental report, tactile-sensory testing, and infrared thermography (IRT). Methods Individuals with NCL (n=8; M age= 14.8 years) and their unaffected siblings (n=8;M age 23.5 years) were characterized in terms of pain response to a brief tactile sensory test (light touch, Von Frey monofilament). During sensory testing, behavioral expression was measured using the Batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These variations in the autonomic responsivity among the aforementioned IDD groups may stem from the IDD etiology; nevertheless, they suggest an overall increased reactivity in IDD. Enhanced behavioral responses to mildly painful calibrated mechanical stimuli were also reported among children with IDD, compared with their siblings [ 24 ] and compared with control children [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations in the autonomic responsivity among the aforementioned IDD groups may stem from the IDD etiology; nevertheless, they suggest an overall increased reactivity in IDD. Enhanced behavioral responses to mildly painful calibrated mechanical stimuli were also reported among children with IDD, compared with their siblings [ 24 ] and compared with control children [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, we found greater pain-evoked potentials among individuals with IDD than in controls, which was correlated with stimulation intensity [ 34 ]; however, this assessment method may not be feasible for clinical purposes. Except for another study in which tactile stimuli produced an increase in facial temperature among children with IDD, compared with controls [ 24 ], we could not find other studies in which physiological indices have been analyzed following experimental noxious stimuli.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pain evaluation through changes in eye temperature has been previously examined in cattle [ 14 , 15 ] and in patients with neuronal ceroid lipofuscinosis [ 19 ]. It has been suggested that eye's temperature measured on the lacrimal caruncle, which estimates the capillary blood flow of the conjunctival bed, when measured by infrared thermography may be a practical and noninvasive measurement of SNS activity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational Pain Scale may be useful for parents monitoring their children's pain at home (74). Transdermal fentanyl has shown some efficacy in reducing centrally mediated pain (75).…”
mentioning
confidence: 99%